2014
DOI: 10.2298/abs1402775s
|View full text |Cite
|
Sign up to set email alerts
|

CsA inhibits IL-22 production by memory CD4+ T cells from patients with psoriasis

Abstract: IL-22 is involved in psoriasis and exacerbates disease progression. Cyclosporine A (CsA) is an immunosuppressant drug that has been used in the treatment of psoriasis for more than 20 years. We determined IL-22 producing T cells and their phenotype, and demonstrated that IL-22 is mainly produced by CD4 + memory T cells not CD8 + T cells in peripheral blood from healthy adults. We compared Th17 and Th1 with the percentages of IL-22 producing CD4 + T cells, and demonstrated that Th1 is the majority Th subset in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Moreover, we found that Th22 subset existed in blood of healthy young children. The above results we observed in children are similar to adults [ 16 , 17 ]. However, we found that the percentages of IL-22 + CD4 + T cells were significantly lower in children than adults.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we found that Th22 subset existed in blood of healthy young children. The above results we observed in children are similar to adults [ 16 , 17 ]. However, we found that the percentages of IL-22 + CD4 + T cells were significantly lower in children than adults.…”
Section: Discussionsupporting
confidence: 88%